Impaired development of intrinsic connectivity networks in children with medically intractable localization‐related epilepsy. Issue 11 (30th June 2014) - Ibrahim, George M.; Morgan, Benjamin R.; Lee, Wayne; Smith, Mary Lou; Donner, Elizabeth J.; Wang, Frank; Beers, Craig A.; Federico, Paolo; Taylor, Margot J.; Doesburg, Sam M.; Rutka, James T.; Carter Snead, O.
Abstract Typical childhood development is characterized by the emergence of intrinsic connectivity networks (ICNs) by way of internetwork segregation and intranetwork integration. The impact of childhood epilepsy on the maturation of ICNs is, however, poorly understood. The developmental trajectory of ICNs in 26 children (8–17 years) with localization‐related epilepsy and 28 propensity‐score matched controls was evaluated using graph theoretical analysis of whole brain connectomes from resting‐state functional magnetic resonance imaging (fMRI) data. Children with epilepsy demonstrated impaired development of regional hubs in nodes of the salience and default mode networks (DMN). Seed‐based connectivity and hierarchical clustering analysis revealed significantly decreased intranetwork connections, and greater internetwork connectivity in children with epilepsy compared to controls. Significant interactions were identified between epilepsy duration and the expected developmental trajectory of ICNs, indicating that prolonged epilepsy may cause progressive alternations in large‐scale networks throughout childhood. DMN integration was also associated with better working memory, whereas internetwork segregation was associated with higher full‐scale intelligence quotient scores. Furthermore, subgroup analyses revealed the thalamus, hippocampus, and caudate were weaker hubs in children with secondarily generalized seizures, relative to other patient subgroups. Our findings underscore that epilepsy interferes with the developmental trajectory of brain networks underlying cognition, providing evidence supporting the early treatment of affected children. Hum Brain Mapp 35:5686–5700, 2014. © 2014 Wiley Periodicals, Inc.